Pengaruh Audit Report Lag, Komite Audit, Financial Health, dan Pertumbuhan Perusahaan terhadap Opini Audit Going Concern - Saighotun Haniyah; Regina Jansen Arsjah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the effect of audit report lag, audit committee, financial condition, and company growth on going concern audit opinion. This study uses a quantitative approach with secondary data obtained from the financial statements of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) with the research year 2021 to 2023, a total of 61 companies included in the research sample lasted for three years resulting in a total of 183 samples obtained by purposive sampling technique. This study uses descriptive statistical analysis, binary logistic regression analysis, hypothesis testing for its analysis. The results of this research analysis indicate that audit report lag has a positive effect on going concern audit opinion, audit committee has no effect on going concern audit opinion, financial health has a negative effect on going concern audit opinion, and company growth has no effect on going concern audit opinion.